Amniotic membrane extract and eye drops: a review of literature and clinical application - Murri MS (Dove Medical Press, 2018)
Michael S Murri,1 Majid Moshirfar,1,2 Orry C Birdsong,2 Yasmyne C Ronquillo,2 Yanning Ding,2 Phillip C Hoopes2 1John A Moran Eye Center, Department of Ophthalmology and Visual Sciences, University of Utah School of Medicine, Salt Lake City, UT, USA; 2HDR Research Center, Hoopes Vision, Draper, UT, USA Abstract: The amniotic membrane (AM) has a long history of use in the treatment of various diseases of the ocular surface. It contains pluripotent cells, highly organized collagen, anti-fibrotic and anti-inflammatory cytokines, immune-modulators, growth factors, and matrix proteins. It is used to promote corneal healing in severely damaged eyes. Recently, AM extract and AM extract eye drops have been successfully used in clinical applications, including dry eye and chemical burns. We provide an overview on the recent progress in the preparation, mechanisms of action, and use of AM extract/AM extract eye drops for corneal and external eye diseases. Keywords: amniotic membrane, amniotic membrane extract, amniotic membrane extract eye drops, AME, AMEED, AMT, umbilical cord, amnion, Regenesol, Genesis, Regener-Eyes, corneal wound healing, amniotic membrane transplant